An Analysis of "来/去" Errors in Chinese Directional Complements by Indonesian Students - Marsuki, Ria Riski; Waru, Dian Sari Unga; Septevany, Elvira; Fatmawati, Fatmawati (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
Mandarin Chinese directional complements present a significant and well-documented challenge for Indonesian learners. This study delves into the intricacies of this grammatical aspect, aiming to identify the specific difficulties encountered by Indonesian students and to propose effective pedagogical strategies. The research employs a mixed-methods approach, beginning with a comparative linguistic analysis of complement expression in both Mandarin Chinese and Indonesian to pinpoint potential areas of linguistic interference. Subsequently, a questionnaire is administered to Indonesian students learning Mandarin to gather empirical data on their comprehension and application of directional complements. Furthermore, a detailed error analysis is conducted on student-produced language samples, focusing specifically on the use of “来/去” (lái/qù) and other directional complement structures. The findings of this study illuminate the multifaceted reasons behind the observed errors, encompassing negative transfer from the learners' first language, individual learner variables such as learning styles and aptitude, environmental factors influencing language acquisition, and the potential inadequacies of current teaching materials and methodologies. Ultimately, this research culminates in the formulation of targeted teaching suggestions and practical methods designed to mitigate these challenges and enhance the learning experience for Indonesian students striving to master Chinese directional complements.